Molecular epidemiology of South African serotype 3 and serotype 19A pneumococcal isolates - Mothibeli, Kedibone Maria (My University, 2008)
The clonality of a random sample of 102 invasive pneumococcal serotype 3 strains isolated from Gauteng Province during January 2000 to December 2003 was investigated. Pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) revealed a heterogeneous population with several PFGE clusters and sequence types (STs). The largest PFGE cluster comprised 36/102 (35%) isolates including seven that belonged to ST458, a clone that is not common in other parts of the world. The global clone (ST180) which is common in the United States and other countries was found in a cluster that represented only 14/102 (14%) of isolates examined. The first multidrug-resistant pneumococcal serotype 19A strain that was isolated in South Africa in 1977 was compared with invasive serotype 19A multidrug-resistant strains isolated in South Africa during June 1999 to December 2004. PFGE analysis of these isolates demonstrated clonal diversity among the isolates. MLST of 16 randomly selected isolates revealed several STs, none of which was the same ST as the 1977 clone. Both serotype 3 and 19A were not associated with increased mortality or HIV seropositivity compared to other serotypes.
Keywords: pneumococcus; serotype 3; serotype 19A